The Effect of School Efficiency on Student Achievemen - Ahmet Kanmaz; Lütfi Uyar (International Journal of Assessment Tools in Education)
This study was based on the views of teachers of secondary school was carried out to determine the effects on student achievement levels of effectiveness. A scale developed for the purpose, the town of Denizli Çameli the spring semester of 2013-2014 academic year, teachers working in secondary school applied to image.The data obtained from the scales werea nalyzed by SPSS 17.0 statistical software. Determining the properties of a descriptive analysis of the frequency and percentage of teachers participating in the study, the views of the effectiveness of schoo lstatistics were used in determining the mean and Standard deviation. Exchange of views regarding the effectiveness of school based on the study of descriptive characteristics of teachers, t test, one-way ANOVA andTukey tests used. Determine the success of students in the determination of the effectiveness of TEOG regression analysis was applied on the results of the school.Result of research, they found highly effective teachers in schools, teachers' observations on the differences according to descriptive characteristics determined to be an effective school. Significant effects on student achievement of teachers' views of the effectiveness of the school were not observed.